2022
DOI: 10.3390/ijerph192416837
|View full text |Cite
|
Sign up to set email alerts
|

Fast Pyrolysis of Cellulose and the Effect of a Catalyst on Product Distribution

Abstract: Fast pyrolysis of microcrystalline cellulose (MC) was carried out by pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). The effects of temperature, time, and a catalyst on the distribution of the pyrolysis products were analyzed. The reaction temperature and time can significantly affect the types and yields of compounds produced by cellulose pyrolysis. A pyrolysis temperature of 500–600 °C and pyrolysis time of 20 s optimized the yield of volatile liquid in the pyrolysis products of cellulose. In all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, only one study reported that HZSM-5 promoted the formation of carbohydrates. However, they did not investigate or explain the reaction mechanism behind such a finding …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only one study reported that HZSM-5 promoted the formation of carbohydrates. However, they did not investigate or explain the reaction mechanism behind such a finding …”
Section: Resultsmentioning
confidence: 99%
“…However, they did not investigate or explain the reaction mechanism behind such a finding. 108 Maliekkal et al explained the importance of the hydroxyl group of glucose in aiding LGA formation during CE pyrolysis. They explained that the breakage of the α-glycosidic bond of CE gave a glucose molecule and an epoxy end.…”
Section: Ce Vs D-glucosementioning
confidence: 99%